Trans-national identities, modes of networking and integration in a multi-cultural society: A study of migrant Bangladeshis in Peninsular Malaysia - Nayeem Sultana (University of Bonn, Center for Development Research (ZEF), 2007)
Nation is defined as an 'imagined community' (Benedict Anderson 1991) of the inhabitants of a country that shares a common sense of identity. Among the migrant Bangladeshis in Malaysia, consisting of very diverse groups of people, a common national identity as Bangladeshi citizens or Malaysians is not a reality. Rather, the nurturing of class interests and exploitation as well as regionalism and affiliation with local power brokers are very common. Along with this the formation of hybrid trans-national identities through integration and interaction with the multi-ethnic population of Malaysia, is another reality. Networking is identified as a major survival strategy, but it is motivated by the then social reality. This paper will explore how people attempt to survive in Malaysia under these socially diverse conditions
urn:nbn:de:0202-20080911215
Keywords: 300